Uncommon presentation of primary hyperaldosteronism with severe hypomagnesemia: a Gitelman syndrome mimic - Phatharaporn Kiatpanabhikul; Wasakorn Bunyayothin (Renal Failure, 2019)
Primary hyperaldosteronism (PA) usually presents with moderate to severe hypertension with or without hypokalemia in adults. However, PA is not commonly associated with severe hypomagnesemia. By contrast, Gitelman syndrome usually presents with clinical manifestations of hypokalemia and hypocalcemia due to hypomagnesemia. Here, we present the case of a 44-year-old woman who first presented with peripheral paresthesia. Her laboratory tests revealed severe hypokalemia, metabolic alkalosis, severe hypomagnesemia, hypocalcemia and secondary hyperparathyroidism. The patient took high dose KCL tablets and Mg tablets to maintain normal values. She took only low-dose hydralazine to maintain normal blood pressure. Further investigations revealed PA with a left adrenal tumor. After left adrenalectomy, she remained in a normotensive, normokalemic and normomagnesemic state without any medical supplements. Thus, PA should be considered in patients with severe hypomagnesemia without moderate to severe hypertension.